Nanomagnetite-Zeolite Composites in the Removal of Arsenate from Aqueous Systems - Escudey-Castro, A; Escudey-Castro, A; Rubio-Campos, M; Pizarro-Arriagada, C; Pizarro-Arriagada, C; Muñoz-Lira, D; Muñoz-Lira, D; Albornoz-Andrade, M; Albornoz-Andrade, M; Casagrande-Denardin, J (Sociedade Brasileira de Quimica, 2015)
Composites based on nanosized particles of magnetite and natural microsized zeolite were prepared and their efficiency to adsorb arsenate from aqueous systems was evaluated through kinetic data and adsorption isotherms, considering the proportion of magnetic iron oxide, composite:solution ratio and zeolite particle size. A well-crystallized nanomagnetite with an averaged particle size of 50 nm when supported on zeolite was obtained; the nanomagnetite enhances the arsenate adsorption of zeolite. The composite prepared with a nanomagnetite:zeolite mass ratio of 0.43:1 and 0.30:1 presented on zeolite milled 20 and 120 min, respectively, showed a similar adsorption capacity as that observed for pure magnetite. Supported nanomagnetite prevents risks of the nanoparticles contamination. The smaller the mean particle size of zeolite the lower the mass proportion of nanomagnetite in the composite required to reach the maximum adsorptive efficiency. Acidic conditions improve arsenate remotion, in agreement with the development of positive surface charge in the composite. © 2015 Sociedade Brasileira de Química.